The Effects of Environmental Performance, Profit Margin, Firm Size, and Environmental Disclosure on Economic Performance - Andriana, Adhe Eva; Anisykurlillah, Indah (Accounting Analysis Journal, 2019)
This study aims to identify the effects of environmental performance, profit margin, and firm size to economic performance, and its effect mediated by environmental disclosure. The population are mining and oil and gas companies listed on the Indonesia Stock Exchange from 2013 to 2017 in the amount of 38 companies. The sample selection used purposive sampling technique and obtained 10 companies with 50 units of analysis. The data analysis techniques in this research were Path Analysis and Sobel Test. The results indicate that environmental performance and environmental disclosure have significant positive effect on economic performance. Profit margin and firm size do not have significant effect on economic performance. Environmental performance and firm size have no significant effect on economic performance through environmental disclosure. Profit margin has a significant effect on economic performance through environmental disclosure. The conclusions in this study indicate that the higher level of environmental performance and environmental disclosure lead to the higher level of economic performance. In addition, the higher level of profit margin leads to the higher level of environmental disclosure, as the result the level of economic performance gained.